(untitled) (مجلة الواحات للبحوث والدراسات, 2025)
For the sake of knowing the causes and results of language contact an rivalry in Algeria, this paper is interested in the development and the contact of Berber, Arabic, French and English. In addition, it focuses on how these languages influence one another and cause changes on each other in one of the academic contexts. It also focuses on the different mechanisms of language change. For that, an observational evaluation of the developmental stages in the teaching of translation for first-year Master students of English is used as a method because translation is the best area where different languages meet and influence one another. As a result, multitude of languages are used among the chosen population. Although the use of these languages is different from one student to another, they meet in one spot, which is the translation process. Keywords: Language contact, multilingualism, Algeria, translation, First year Master students.